Computing with Social Trust - Golbeck, Jennifer (Springer, 2017)
As open, distributed systems like the Web continue to grow, and more and more content created by users becomes available, the question of whom and what can be trusted becomes increasingly important. This book looks at one solution – social trust relationships – and examines the challenging research problems raised by computing with social trust. (...)